Cholesterol Efflux Pathways Regulate Myelopoiesis: A Potential Link to Altered Macrophage Function in Atherosclerosis - Murphy, Andrew James; Dragoljevic, Dragana; Tall, Alan Richard (Frontiers in Immunology, 2014)
Atherosclerotic cardiovascular disease (CVD) is a chronic inflammatory disease of the blood vessels that can lead to myocardial infarction or stroke. The major cell in the atherosclerotic lesion, the macrophage is thought to be an important contributor to the production of inflammatory mediators that exacerbate this disease. Macrophages are generally derived from circulating monocytes, which are in turn produced by hematopoietic stem and multipotential progenitor cells (HSPCs) in the bone marrow and other medullary organs. Recent studies suggest that disruption in cholesterol homeostasis or prolonged exposure to a hypercholesterolemic environment can influence HSPCs to over-produce monocytes, resulting in monocytosis. These monocytes may carry a pre-programed ability to become M1-like macrophages once they enter the atherosclerotic lesion. Future studies may help to differentiate the role of such pre-programming versus responses to local environmental cues in determining M1, M2 or other macrophage phenotypes in atherosclerotic lesions.